(3x - 2)(x + 8)

It is: 3x*(x+7)

x(3x + 1)

(3x + 1)(x + 5)

3(x2 + 3x + 1)

(3x + 1)(3x + 1)

(x + 5)(3x + 1)

(3x - y+ 2)(3x + y + 2)

(3x + 3y)(x + y) = 3(x + y)2

(6x + t)(3x + t)

If that's -18y2, the answer is (3x - 2y)(x + 9y)

6xyz(3x + 2y + z)

(3x - 1)(x + 2)

(3x - 2)(x + 4)

3x2 + 10x + 3 = (x + 3)(3x + 1).

(3x - y - 9)(3x - y + 9)

2x(3x + 5)

It is: x(x+3)

(x - 1)(3x + 5)

3x2+10x+7 = (3x+7)(x+1) when factored

3x^2 -14x +15 = (3x-5)(x-3)

(x + 2)(x + 1)

20x2 - 3x + 10 does not have any real factors.

(x + 3)(3x - 2)

3x 2 + 2x - 5 = (x - 1)(3x + 5).

3(x + 4)(x + 1)

3x3+15x2+18x = 3x(x2+5x+6) = 3x(x+2)(x+3)

x2 - 3x + 2 = (x - 2)(x - 1)

The expression does not have rational factors.

(x^2 - 3x + 5)(x^2 + 3x + 5)

x(5x^2 - 3x + 2)

The factors are [3x + 5 - 2*sqrt(10)] and [3x 5 + 2*sqrt(10)].

Let the symbol ^ mean "to the power" Then 9x^2 + 24x + 16 = (3x + 4)(3x +4) = (3x + 4)^2

(x - 6)(x + 9)

-15x2+5x=-5x(3x-1)

(x + 9)(x - 6)

(x - 2)(2x + 7)

4x(4x^2 + 3x + 1)

(x + 2)(3x - 1)(3x + 1)

3x^2+3x-60=3(x^2+x+20)=3(x+5)(x-4)

5x2 + 3x + 8x2 = 13x2 + 3x = x(13x + 3)

The given expression can be simplified to: 3X squared +27

3(x - 8)(x - 6)

2(5x - 1)(3x - 2)

9x(x2+3x-10)

the answer is (3x-2)(9x squared+6x+4)

Assuming that's 9x2, it factors to (3x - 5i)(3x + 5i) where i is the square root of -1.

9X2 = 3X(3X) Best I can see to factor here.

If that's -5, the answer is (x - 1)(3x + 5) If that's +5, it gets ugly in a hurry.

(x + 8)(x - 5)

It can't be factored because the discriminant of this quadratic expression is less than zero.